Succession planning and family business longevity: a study on currency exchange companies - Soelistyawati, Soelistyawati; Mujanah, Siti; Ridwan, Mochammad Sihab (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This study investigates the critical determinants influencing the longevity of family businesses, particularly within the context of Money Changers in East Java, Indonesia. The research is grounded in the premise that sustained business success across generations depends on effective succession planning, successor preparation, family commitment, and the involvement of the controlling generation. Using a quantitative approach, the research employs PLS - SEM to analyze the relationships between variables. Data collected from 86 licensed Money Changers in East Java. Findings indicate that succession planning and family commitment significantly influence the involvement of the previous generation in transitioning leadership roles. The research underscores the pivotal role of the controlling generation in ensuring the continuity and stability of family businesses. Recommendations include detailed plans for identifying and preparing successors, enhancing family commitment, and increasing the involvement of the previous generation in decision-making processes. Strengthening these aspects is crucial for ensuring the resilience and long-term viability of family businesses, particularly in the Money Changers sector. Future research should expand its scope to encompass diverse regions and consider customer perspectives to shape robust strategies for sustained family business growth.